Notes on Hernandiaceae: First record of Gyrocarpus americanus Jacq. for Mexico and from Sparattanthelium amazonum Mart. for Oaxaca - Rivera Hernández, Jaime Ernesto (Instituto de Ecología, A.C., 2007)
Gyrocarpus americanus Jacq. is reported for the first time from Mexico, where it grows in the coastal area of Oaxaca; comments are included about its distribution. Sparattanthelium amazonum Mart. is reported for the first time from Oaxaca, where it grows in the region of the Chimalapas.